RETRACTED: OST1 Activation by the Brassinosteroid-Regulated Kinase CDG1-LIKE1 in Stomatal Closure. Issue 8 (31st July 2018) - Kim, Tae-Woo; Youn, Ji-Hyun; Park, Tae-Ki; Kim, Eun-Ji; Park, Chan-Ho; Wang, Zhi-Yong; Kim, Seong-Ki; Kim, Tae-Wuk
Abstract : Brassinosteroid acts synergistically with ABA in guard cells, and CDL1 mediates BR-induced stomatal closure through OST1 activation. Abstract: Crosstalk between signaling pathways is an important feature of complex regulatory networks. How signal crosstalk circuits are tailored to suit different needs of various cell types remains a mystery in biology. Brassinosteroid (BR) and abscisic acid (ABA) antagonistically regulate many aspects of plant growth and development through direct interactions between components of the two signaling pathways. Here, we show that BR and ABA synergistically regulate stomatal closure through crosstalk between the BR-activated kinase CDG1-LIKE1 (CDL1) and the OPEN STOMATA1 (OST1) of the ABA signaling pathway in Arabidopsis thaliana . We demonstrate that the cdl1 mutant displayed reduced sensitivity to ABA in a stomatal closure assay, similar to the ost1 mutant. CDL1 and the BR receptor BR-INSENSITIVE1, but not other downstream components of the BR signaling pathway, were required for BR regulation of stomatal movement. Genetic and biochemical experiments demonstrated that CDL1 activates OST1 by phosphorylating it on residue Ser-7. BR increased phosphorylation of OST1, and the BR-induced OST1 activation was abolished in cdl1 mutants. Moreover, we found that ABA activates CDL1 in an OST1-dependent manner. Taken together, our findings illustrate a cell-type-specific BR signaling branch through which BR acts synergistically with ABA in regulating stomatal closure.